Quantitative analysis of choroidal alterations in thyroid eye disease using swept-source OCT - Dai, Yining; Wang, Kailu; Zheng, Dongping; Li, Guangxu; Wang, Kang; Wang, Xin; Sun, Bin (Frontiers in Physics, 2023)
Purpose: To investigate choroidal alterations in patients with thyroid eye disease (TED) using swept-source optical coherence tomography (SS-OCT) and compare them with age-matched healthy controls. Methods: SS-OCT scans were performed to obtain quantitative measurements of choroidal parameters. Mean choroidal thickness (MCT), choroidal vessel volume (CVV), choroidal stroma volume (CSV), choroidal vascularity index (CVI), and choroidal stroma-to-vessel volume ratio (CSVR) were calculated and compared between TED and control eyes. Results: TED eyes exhibited significantly higher MCT (276.25 ± 58.75 μm vs. 236.86 ± 45.02 μm, p < 0.001), CVV (21.46 ± 5.10 mm3vs. 18.14 ± 3.83 mm3, p = 0.001), and CSV (13.86 ± 2.80 mm3vs. 11.44 ± 2.17 mm3, p < 0.001) compared to control eyes. However, there were no significant differences in CVI (0.61 ± 0.02 vs. 0.61 ± 0.03, p = 0.838) or CSVR (0.65 ± 0.05 vs. 0.64 ± 0.07, p = 0.345) between the two groups. Conclusion: SS-OCT effectively differentiated TED eyes from normal eyes based on choroidal alterations. The increased MCT, CVV, and CSV in TED suggest both dilated choroidal vasculature and expanded choroidal stroma. These findings highlight the potential of SS-OCT as an adjunctive imaging tool for the assessment of TED.